2020
DOI: 10.1016/j.joca.2020.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Differential patterns of pathology in and interaction between joint tissues in long-term osteoarthritis with different initiating causes: phenotype matters

Abstract: Objective: To determine if osteoarthritis (OA) progression and joint tissueepathology associations link specific animal models to different human OA phenotypes. Design: Male 11-week-old C57BL6 mice had unilateral medial-meniscal-destabilization (DMM) or antigen-induced-arthritis (AIA). Joint tissue histopathology was scored day-3 to week-16. Tissue-pathology associations (corrected for time and at week-16) were determined by partial correlation coefficients, and odds ratios (OR) calculated for likelihood of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…(37) Follow-up studies are needed to confirm the presence of a BML in this mouse model and, if present, whether it precedes joint degeneration or is simply co-occurring. Another limitation of this line of investigation is the use of ACL transection, which causes severe changes in joint stability to initiate osteoarthritis (the ACL transection model is classified as "traumatic" in the literature (38,39) ). It is unclear if the same mechanisms identified under this severe traumatic disruption of joint biomechanics are also active in less-severe situations such as nontraumatic OA-associated BMLs.…”
Section: Bone Marrow Lesions In Animal Models Of Posttraumatic Osteoa...mentioning
confidence: 99%
“…(37) Follow-up studies are needed to confirm the presence of a BML in this mouse model and, if present, whether it precedes joint degeneration or is simply co-occurring. Another limitation of this line of investigation is the use of ACL transection, which causes severe changes in joint stability to initiate osteoarthritis (the ACL transection model is classified as "traumatic" in the literature (38,39) ). It is unclear if the same mechanisms identified under this severe traumatic disruption of joint biomechanics are also active in less-severe situations such as nontraumatic OA-associated BMLs.…”
Section: Bone Marrow Lesions In Animal Models Of Posttraumatic Osteoa...mentioning
confidence: 99%
“…One explanation is the current discrepancy between preclinical research predominantly using ptOA models and clinical studies, the majority of which investigate late-stage “primary OA” which occurs in the absence of prior trauma or disease ( 309 ). There is emerging evidence that the pathophysiologic mechanisms of structural and symptomatic OA differs depending on the key initiating factors or disease phenotype ( 310 , 311 ). How different the complex cellular inflammatory response is in different OA phenotypes remains to be resolved.…”
Section: Concluding Remarks Open Questions and Future Directionsmentioning
confidence: 99%
“…Hence, the histopathological studies of OA phenotypes seem quite relevant. Earlier experimental study [18] revealed the relationship between initiating OA mechanisms and structural joint tissues progression in animal models, imitating the development of different human OA phenotypes.…”
Section: Introductionmentioning
confidence: 99%